Behavioural constraints in energy technology uptake: Evidence from real-purchase offers in rural Rwanda and Senegal - Gunther Bensch; Michael Grimm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Energy-efficient biomass cookstoves and small solar systems play a vital role in the transition to clean energy. Despite their affordability and scalability, their uptake remains low among households in sub-Saharan Africa. This paper examines the potential contribution of individual-specific behavioural factors to the under-adoption of these technologies. Drawing on data from real-purchase offers in rural Rwanda and Senegal, the analysis focuses on how the willingness to pay for the technologies varies with behavioural constraints including risk aversion, innovation resistance, time preferences, and beliefs. Our results confirm that these factors carry relevant variation that helps understanding the purchase decision process. These findings contribute to a better comprehension of consumer adoption behaviour of innovative consumer goods at the base of the pyramid, providing valuable insights for suppliers entering these markets and informing policy interventions aimed at facilitating households' transition to clean energy. – – Energieeffiziente Biomasse-Kochherde und Kleinsolarsysteme sind entscheidende Übergangstechnologien bei der Umstellung auf saubere Energieträger. Obwohl sie erschwinglich und skalierbar sind, sind sie in ländlichen Gegenden Afrikas südlich der Sahara nach wie wenig verbreitet. In diesem Beitrag wird untersucht, inwieweit individualspezifische Verhaltensfaktoren zur geringen Verbreitung dieser Technologien beitragen. Auf der Grundlage von Daten aus realen Kaufangeboten im ländlichen Ruanda und Senegal konzentriert sich die Analyse darauf, wie die Bereitschaft, für die Technologien zu zahlen, mit Faktoren wie Risikoaversion, Innovationsresistenz, Zeitpräferenzen und Überzeugungen variiert. Unsere Ergebnisse bestätigen, dass diese Faktoren zum Verständnis des Kaufentscheidungsprozesses beitragen. Diese Ergebnisse liefern ein besseres Verständnis des Kaufverhaltens von armen Verbrauchern im Hinblick auf innovative Konsumgüter bei. Sie liefern wertvolle Erkenntnisse für Anbieter, die diese Märkte erschließen, und liefern Informationen für Politikmaßnahmen, die darauf abzielen, den Übergang von Haushalten zu sauberer Energie zu erleichtern.
Keywords: D12; O12; O13; O33; Q41; 330; Base of the pyramid; energy transition; willingness to pay; household decision; behaviour